AKTIVITAS MENULIS FANFICTION DI WATTPAD SEBAGAI PRODUKTIVITAS DARI FANDOM EXO - Sinarsi, Mersi (Commsphere: Jurnal Ilmu Komunikasi, 2024)
The EXO, a South Korean boy group that is currently trending, has succeeded in building a large fan base with the fandom name EXO-L. This article explores the phenomenon of fandom creativity, especially the activity of writing fanfiction, as an expression of fans' love and dedication to their idols. In this article, the fanfiction “Manage your Manager (EXO FANFICTION)” on Wattpad is a popular example that achieved high rankings and is proof of the positive impact on fan identity. By utilizing the Fan Motivation Theory proposed by Wann, this article reveals the motivational factors that drive EXO-Ls to write fanfiction, such as eustress, escapism, aesthetic pleasure, entertainment, cultural connection, self-esteem, and even potential economic gain. The research method used is descriptive qualitative with data collection through literature study and observation of online reading media platforms, especially Wattpad. In addition to illustrating the productivity of fandom, this article highlights the positive benefits of fanfiction, including the development of writing talent and contribution to idol popularity. This article concludes that fanfiction, apart from being a form of creative expression, also acts as a promotional tool and introducing idols to a wider audience. The fanfiction phenomenon in EXO-L not only creates space for creativity, but also deepens and enriches the relationship between fans and their idols. This conclusion emphasizes the complexity and diversity of motivations behind fanfiction which ultimately makes a positive contribution to the dynamics and sustainability of EXO-L fandom. Keywords: EXO, EXO-L, FanFiction, Wattpad